A survival case of intravenous paraquat intoxication: A case report. Issue 30 (July 2018) - Chen, Chi-Wei; Wu, Yen-Hung; Chien, Shun-Ching; Lin, Jhong-Ching
Abstract: Rationale: Paraquat, an agent highly toxic to humans and animals, is a widely used herbicide and also commonly used for suicide attempts in Taiwan. The most common route of intoxication is oral ingestion, and parenteral poisoning is respectively rare. Patient concerns: A 39-year-old illicit abuser of heroin and amphetamine injected 0.5 mL of 24% paraquat directly into his right cephalic vein due to hallucination. The patient was brought to our emergency department for management 4 hours after injection. He was fully conscious and had normal vital signs. Systemic review showed mild dyspnea, abdominal pain and right wrist pain over the injection site. The only abnormal physical finding was erythema over the injection site and epigastric tenderness. Diagnosis: Laboratory investigations, including complete blood count, liver and renal function, and electrolytes initially yielded normal results. Urinalysis showed normal findings except a positive urine paraquat test (4+). The initial plasma paraquat concentration was 0.51 μg/mL. Interventions: He was admitted to the intensive care unit and underwent one session of charcoal hemoperfusion therapy. Acute kidney injury developed on the fourth day after intoxication, with the level of serum creatinine rising rapidly from 0.96 to 4.57 mg/dL and the daily urine output decreased noticeably from > 2000 to 900 mL. The serum creatinine level improved gradually with adequate fluid supplementation. Outcomes: The patient was discharged 13 days later in a stable condition. Lessons: Intravenous paraquat intoxication is rare. Patients who suffer from intravenous intoxication may not directly suffer from mucosal irritation, but the clinical onset of systemic effects is more immediate and lethal. The prognosis of paraquat poisoning is determined by the time of poisoning and the plasma paraquat concentration before treatment. Proudfoot's curve provides a simple method of predicting the survival rate. The most effective mode of management is extracorporeal therapy, and immunosuppressive or antioxidant therapies have shown insufficient evidence of benefit.